Soybean Biochemistry, Chemistry and Physiology - Ng, Tzi-Bun (IntechOpen, 2011)
Soybean is an agricultural crop of tremendous economic importance. Soybean and food items derived from it form dietary components of numerous people, especially those living in the Orient. The health benefits of soybean have attracted the attention of nutritionists as well as common people.